Предмет: Алгебра,
автор: eld21122014032
Представьте в виде многочлена:
(2х+5)(4+3х)
(1-а)(5а+6)
Ответы
Автор ответа:
4
первое выражение
8х + 6х² + 20 + 15х = 6х² + 23х + 20
второе выражение
5а + 6 - 5а² - 6а = 6 - 5а² - а
8х + 6х² + 20 + 15х = 6х² + 23х + 20
второе выражение
5а + 6 - 5а² - 6а = 6 - 5а² - а
Автор ответа:
2
(2х+5)(4+3х)=8х+6х^2+20+15х=6х^2+23х+20
(1-а)(5а+6)=5а+6-5а^2-6а=-5а^2-а+6
(1-а)(5а+6)=5а+6-5а^2-6а=-5а^2-а+6
Похожие вопросы
Предмет: Українська література,
автор: irshama
Предмет: Английский язык,
автор: nekitkuznetsov1
Предмет: Английский язык,
автор: Kirill13377
Предмет: Английский язык,
автор: Avlezhinzaiab
Предмет: История,
автор: ohmygod19
2)5а + 6 - 5а^2 - 6а = 6 - 5а^2 - а